2012
DOI: 10.1248/bpb.b212013
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Mediated Delivery of Anticancer Agents to Tumor Angiogenic Vessels

Abstract: Nanoparticle-mediated drug delivery systems targeting tumor angiogenic vessels have been studied for antineovascular cancer therapy achieved by induction of apoptosis of angiogenic endothelial cells. Nanoparticles such as liposomes are considered to accumulate in tumors due to the enhanced permeability and retention effect. The delivery efficiency of this system appears to be affected by the density of tumor angiogenic vessels regardless of modification with tumor-targeting ligands on the surface of nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 27 publications
0
24
0
3
Order By: Relevance
“…2) This phenomenon is referred to as enhanced permeability and retention (EPR) effects of nano-DDS. 27) Recognition and incorporation by the mononuclear phagocyte system (MPS, also called the reticuloendothelial system), namely neutrophils, monocytes, and macrophages in the blood, liver, spleen, and lymph nodes is also a common physiological behavior for nano-DDS, which may affect the blood circulating time and tissue/cell distribution. [28][29][30][31] One of the first clinically approved nano-scale DDS therapies was a liposomal formulation of doxorubicin, a cytotoxic drug used for cancer chemotherapy.…”
Section: Physiological Behavior Of Nano-ddsmentioning
confidence: 99%
“…2) This phenomenon is referred to as enhanced permeability and retention (EPR) effects of nano-DDS. 27) Recognition and incorporation by the mononuclear phagocyte system (MPS, also called the reticuloendothelial system), namely neutrophils, monocytes, and macrophages in the blood, liver, spleen, and lymph nodes is also a common physiological behavior for nano-DDS, which may affect the blood circulating time and tissue/cell distribution. [28][29][30][31] One of the first clinically approved nano-scale DDS therapies was a liposomal formulation of doxorubicin, a cytotoxic drug used for cancer chemotherapy.…”
Section: Physiological Behavior Of Nano-ddsmentioning
confidence: 99%
“…[23][24][25][26] In this type of therapy, anticancer drugs are expected to be efficiently delivered to angiogenic endothelial cells, since such drugs contained in liposomes firstly meet blood vessels after injec- Naoto Oku tion of them into bloodstream and, thus, easily interact with them. 27,28) Lipid composition and characteristics of liposomes used for ANET and other studies described in the review are shown in Table 1. Recently, Hansen et al determined the distribution of copper-64 encapsulated in PEGylated liposomes and evaluated the EPR effect in 11 canine cancer patients with spontaneous solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…In tumor tissues, immature lymphatic vessels retard elimination of nanoparticles. These effects are known as enhanced permeability and retention effects 22,23) . Surface modification with polyethylene glycol (PEG) prevents entrapment of nano particles by the reticuloendothelial system due to its hydrophilic property.…”
mentioning
confidence: 99%